Epidemiology of Falls in Older Adults in Texas. Issue 2 (February 2015) - Alamgir, Hasanat; Wong, Nicole J.; Hu, Yueha; Yu, Mo; Marshall, Amanda; Yu, Shicheng
Abstract : Objectives: The expected increase in the US older adult population implies an increased risk of fall-related injury among these individuals. We describe the epidemiology of fall morbidity among older adults in Texas, a large US state with a diverse population base. Methods: Texas Behavioral Risk Factor Surveillance System 2010 data were analyzed. The falls outcome was defined as falling: any fall in the past 3 months and a serious fall: a fall resulting in limited activities for at least 1 day or requiring medical attention. Results: A total of 5996 subjects were included in this analysis; 17.6% (n = 1055) reported falling 1 to 5 times in the previous 3 months, and 361 (6%) experienced serious falls. Risk of falling had a significant positive association among respondents who rated their general health as fair to poor (relative risk [RR] 2.39, 95% confidence interval [CI] 1.55–3.68) and a negative association for those who reported regular physical activity (RR 0.59, 95% CI 0.42–0.82). A similar model examined the risk of serious falls and found statistically positive associations in respondents who reported fair or poor general health (RR 3.29, 95% CI 2.00–5.43). Negative associations were found for those who reported regular physical activity (RR 0.56, 95% CI 0.38–0.83) and for men (RR 0.62, 95% CI 0.39–0.98). No statistically significant correlations for either of the fall outcomes were found with residence, obesity, education, income, age, ethnicity, employment, marital status, diabetes mellitus, or cardiovascular disease. Conclusions: Interventions aimed at the prevention of falls should focus on maintaining and improving general health and promoting physical activity among older adults. Abstract : The expected increase in the older adult population in the United States implies an increased risk of fall-related injury among these individuals. This article describes the epidemiology of fall morbidity among older adults in Texas, a large US state with a diverse population base. The risk of falling had a significant positive association among respondents who rated their general health as fair to poor and a negative association for those who reported regularly participating in physical activity. A similar model examined the risk of serious falls and found statistically positive associations in respondents who reported fair or poor general health and negative associations for those who reported regular physical activities and male sex. Interventions aimed at the prevention of falls among older adults should focus on maintaining and improving their general health and promoting physical activity.